Automatic determination of the frequency behaviour of the larynx tone by the method of linear prediction - DZIURNIKOWSKI, Andrzej (Archives of Acoustics, 1980)
This paper presents a method of automatically tracing the frequency of the larynx tone, based on a numerical implementation of the method of linear prediction on a digital computer. It also discusses the algorithm for the practical implementation of this method, derived by the author, and presents the results obtained from the analysis of a continuous speech signal with a duration of approximately 2 seconds.